Question
upstudy study bank question image url

Hence, or otherwise, write \( -4+3+10+\ldots+486 \) in sigma notation.

Ask by Simmons Simpson. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The series \( -4 + 3 + 10 + \ldots + 486 \) can be written in sigma notation as: \[ \sum_{k=1}^{71} (7k - 11) \] or \[ \sum_{k=0}^{70} (7k - 4) \]

Solution

To express the series \( -4 + 3 + 10 + \ldots + 486 \) in sigma notation, let's first identify the pattern of the sequence. ### Step 1: Determine the Sequence Pattern The given sequence is: \[ -4, \, 3, \, 10, \, \ldots, \, 486 \] Calculate the difference between consecutive terms: \[ 3 - (-4) = 7 \\ 10 - 3 = 7 \] This indicates that the sequence is **arithmetic** with a common difference \( d = 7 \). ### Step 2: Find the General Term The general term of an arithmetic sequence can be expressed as: \[ a_n = a_1 + (n - 1)d \] where: - \( a_1 = -4 \) (the first term) - \( d = 7 \) (common difference) So, \[ a_n = -4 + (n - 1) \times 7 = 7n - 11 \] ### Step 3: Determine the Number of Terms To find the number of terms (\( n \)) when the last term is 486: \[ 7n - 11 = 486 \\ 7n = 497 \\ n = 71 \] ### Step 4: Write in Sigma Notation Putting it all together, the series can be expressed in sigma notation as: \[ \sum_{k=1}^{71} (7k - 11) \] Alternatively, you can adjust the index to start from 0: \[ \sum_{k=0}^{70} (7k - 4) \] Both representations are correct and represent the same series. **Final Answer:** \[ \sum_{k=0}^{70} \left(7\,k\;-\;4\,\right) \] **Or equivalently:** \[ \sum_{k=1}^{71} \left(7k - 11\right) \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To express the series \( -4 + 3 + 10 + \ldots + 486 \) in sigma notation, we first need to identify the pattern or rule governing this series. Let's observe the sequence: - The first term \( a_1 = -4 \) - The second term \( a_2 = 3 \) - The third term \( a_3 = 10 \) To find the common difference, we calculate: \( a_2 - a_1 = 3 - (-4) = 7 \) \( a_3 - a_2 = 10 - 3 = 7 \) Each term increases by 7. Thus, the sequence can be described by the formula for the \( n \)-th term: \[ a_n = -4 + 7(n-1) \] Simplifying this gives us: \[ a_n = 7n - 11 \] Next, we need to determine how many terms there are in the sequence that ends at 486. We can set our formula equal to 486 and solve for \( n \): \[ 7n - 11 = 486 \] \[ 7n = 497 \] \[ n = \frac{497}{7} = 71 \] Thus, there are 71 terms in total. Finally, we can express the sum in sigma notation: \[ \sum_{n=1}^{71} (7n - 11) \] This compactly represents the series \( -4 + 3 + 10 + \ldots + 486 \) in sigma notation!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy